Defining severe familial hypercholesterolaemia and the implications for clinical management: a consensus statement from the International Atherosclerosis Society Severe Familial Hypercholesterolemia Panel. Issue 10 (October 2016) - Santos, Raul D; Gidding, Samuel S; Hegele, Robert A; Cuchel, Marina A; Barter, Philip J; Watts, Gerald F; Baum, Seth J; Catapano, Alberico L; Chapman, M John; Defesche, Joep C; Folco, Emanuela; Freiberger, Tomas; et al.
Summary: Familial hypercholesterolaemia is common in individuals who had a myocardial infarction at a young age. As many as one in 200 people could have heterozygous familial hypercholesterolaemia, and up to one in 300 000 individuals could be homozygous. The phenotypes of heterozygous and homozygous familial hypercholesterolaemia overlap considerably; the response to treatment is also heterogeneous. In this Review, we aim to define a phenotype for severe familial hypercholesterolaemia and identify people at highest risk for cardiovascular disease, based on the concentration of LDL cholesterol in blood and individuals' responsiveness to conventional lipid-lowering treatment. We assess the importance of molecular characterisation and define the role of other cardiovascular risk factors and advanced subclinical coronary atherosclerosis in risk stratification. Individuals with severe familial hypercholesterolaemia might benefit in particular from early and more aggressive cholesterol-lowering treatment (eg, with PCSK9 inhibitors). In addition to better tailored therapy, more precise characterisation of individuals with severe familial hypercholesterolaemia could improve resource use.